Hydrofluoric acid and nitric acid cotreatment for biofunctionalization of polyetheretherketone in M2 macrophage polarization and osteogenesis. Issue 6 (24th August 2020) - Huo, Shicheng; Meng, Xiangchao; Zhang, Shutao; Yue, Bing; Zhao, Yaochao; Long, Teng; Nie, Bin'en; Wang, You
Abstract: Due to its excellent mechanical and low‐friction properties, polyetheretherketone (PEEK) has been widely investigated for use in orthopedic applications over the past decade. However, the bioinertness and poor osteogenic properties of PEEK have hampered its clinical application. In this study, the surface of PEEK was modified by co‐treatment with hydrofluoric acid and nitric acid (AFN). The microstructures of the modified PEEK surfaces were investigated using scanning electron microscopy. The water contact angles of the surfaces were also measured. To evaluate their cytocompatibility, PEEK samples were used as substrates to culture rat bone mesenchymal stem cells, and cell adhesion, viability, and expression of specific marker genes were measured. Treatment of PEEK with AFN (PEEK‐AFN) was found to enable better osteoblast adhesion, spreading, and proliferation; the activity of alkaline phosphatase (an early osteogenic differentiation marker) was also found to be enhanced post‐treatment. Furthermore, PEEK‐AFN was able to modulate macrophage polarization and down regulated the expression of proinflammatory factors via inhibiting the NF‐κB pathway. Thus, treatment of PEEK with AFN could promote M2 polarization of the macrophages and stimulate the differentiation of osteoblasts. These results provide valuable information that could facilitate the use of PEEK‐based composites as bone implant materials.